BIROKRASI, GOOD GOVERNANCE SERTA ARTI MAKNA PENDIDIKAN POLITIK - Abdul Hijar Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Realizing good governance, the Indonesian government, both central and regional, needs to immediately carry out bureaucratic reforms that are not only at the level of commitment but also at the level of real life. It is hoped that this will reduce bureaucratic pathologies such as mal-administration that leads to corruption, collusion, and nepotism. Max Weber's legal rational bureaucracy concept is actualized in Indonesia with various advantages and disadvantages as seen from the behavior of the bureaucracy. Bureaucratic behavior arises when there is an interaction between individual characteristics and bureaucratic characteristics; especially with the various issues that are developing and current law enforcement related to bureaucratic pathology. Gradually, in Indonesia, bureaucratic reform is carried out in the dimensions of institutions, apparatus resources, management, and culture/mind set. Both the central government and local governments should carry out bureaucratic reform through consistent and sustainable learning organizations, taking into account critical success factors.